HRP2 and HRP3 cross-reactivity and implications for HRP2-based RDT use in regions with Plasmodium falciparum hrp2 gene deletions - Amy Kong; Scott A. Wilson; Yong Ah; Douglas Nace; Eric Rogier; Michael Aidoo (Malaria Journal, 2021)
Abstract Background The Plasmodium falciparum antigen histidine rich protein 2 (HRP2) is a preferred target for malaria rapid diagnostic tests (RDTs) because of its abundant production by the parasite and thermal stability. As a result, a majority of RDTs procured globally target this antigen. However, previous reports from South America and recent reports from sub-Saharan Africa and Asia indicate that certain P. falciparum parasites have deletions of the gene coding for HRP2. The HRP2 antigen is paralogous to another P. falciparum antigen HRP3 and some antibodies to HRP2 cross-react with HRP3. Multiple parasites have been described with deletions of one or both hrp2 and hrp3 genes. It is unclear how the various combinations of hrp2 and hrp3 deletion genotypes affect clinical sensitivity of HRP2-based RDTs. Methods Cross-reactivity between HRP2 and HRP3 was tested on malaria RDTs using culture-adapted P. falciparum parasites with both hrp2 and hrp3 intact or with one or both genes deleted. Ten-fold serial dilutions of four culture-adapted P. falciparum parasites [3D7 (hrp2+/hrp3+), Dd2 (hrp2−/hrp3+), HB3 (hrp2+/hrp3−) and 3BD5 (hrp2−/hrp3−)] ranging from 100,000 to 0.01 parasites/µL were prepared. HRP2, Plasmodium lactate dehydrogenase (pLDH) and aldolase concentrations were determined for the diluted samples using a multiplex bead assay. The samples were subsequently tested on three RDT products designed to detect P. falciparum by HRP2 alone or in combination with pLDH. Results At parasite densities of approximately 1000 parasites/µL, parasites that expressed either hrp2 or hrp3 were detected by all three RDTs. Multiplex based antigen measurement using HRP2- conjugated beads demonstrated higher antigen concentration when both hrp2 and hrp3 genes were intact (3D7 parasites, 47.9 ng/ml) compared to HB3 (3.02 ng/mL) and Dd2 (0.20 ng/mL) strains that had one gene deleted. 3D7 at 10 parasites/µL (0.45 ng/mL) was reactive on all three RDT products whereas none of the other parasites were reactive at that density. ...